Ruks-I-Oun Warming Blanket - Khamcharoen, Sakawduean (Journal of Health Science of Thailand, 2017)
Complication from hypothermia is an important problem of operation process especially in high-risk patients. Forced-air warming blanket is a major part of temperature control for hypothermia prevention. Ratchaburi hospital innovated reused material warming blanket (Rux-I-Oun) to replace the commercial ones. The process started with reviewing the property of reused material and testing efficacy of Rux-I-Oun warming blanket compared with the commercial ones. It was found that the quality of temperature control was the same. We have 4 designs which are utilityspecific for all group of patients. They can both cover and/or lay under the patient’s body for highest effectiveness of temperature control. The Rux-I-Oun warming blanket helps increase the temperature of the patient via conduction and convection. A descriptive research was conducted by reviewing anesthetic records of the patients of operation room number 2, during 17 October - 11 November 2011, to calculate the proportion of hypothermia, and analyzing the unit cost comparing to the commercial one. In all, 59 study populations including 36 children (61%) and 23 adults (39%) were included. It was found that 2 patients who had hypothermia (3.4%). Burn complication was not found. On unit cost, this invention had unit cost over 10 times lower than that of the commercial one. The specific types of blankets arechosenproperly with the patients, is an important part of efficiency improvement for hypothermia prevention and highest quality in patient safety aspect.